Analysis of Education Policies in Countering Radicalism: Implementation and Externalization of Islamic Religious Education Values in Shaping Character - Muhammad Arif Rahman Rahman; Subai Subai; Nada Shofa; Encep Syarifudin; Cucu Atikah (STAI Miftahul Ula Nganjuk, 2023)
Radicalization is one of the dangerous effects of globalization. The development of positive character in adolescents is necessary to combat radicalism. The values of Islamic religious education can be internalized and externalized through learning activities both inside and outside the classroom. The aim of this research is to examine how the internalization and externalization of Islamic religious education values influence students' character in combating radicalism. With the population of all high school students from the Islamic Village Foundation in Tangerang, this research adopts a quantitative method, using a proportional random sample of 350 students. After collecting the data, analysis is conducted using the structural equation modeling (SEM) based on partial least squares (PLS). The research results indicate that the internalization and externalization of Islamic religious education values have an influence on students' character and can counteract radicalism.